A hard carbon material and its preparation method and use

By rapidly heating up and dehydrating in the acid solution and carbonizing soluble carbohydrates at high temperature, hard carbon materials with large carbon layer spacing and disordered structure were prepared, which solved the shortcomings of hard carbon materials in the prior art in terms of energy density and power density, and achieved the unity of high-quality/volume specific capacity and high rate performance.

CN115360348BActive Publication Date: 2025-04-25BEIJING UNIV OF CHEM TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202210880395.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-07-25
Publication Date
2025-04-25
Estimated Expiration
2042-07-25

AI Technical Summary

Technical Problem

Existing hard carbon materials have challenges in improving the energy density and power density of lithium-ion and sodium-ion batteries, especially in achieving a unified high-quality/volume specific capacity and high rate performance.

Method used

By dissolving soluble carbohydrates in an acid solution, rapidly heating and dehydration are used to obtain a pre-carbonization precursor, and carbonizing at high temperature in an inert atmosphere, a hard carbon material with a large carbon layer spacing and disordered structure is prepared.

Benefits of technology

It has achieved high specific capacity and excellent rate performance of hard carbon materials, and promoted the high rate charge and discharge capacity and industrial development of lithium-ion batteries and sodium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115360348B_ABST
    Figure CN115360348B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of battery technology, and in particular to a novel hard carbon material, a preparation method thereof, and a use thereof. The preparation method of the hard carbon material of the present invention comprises the following steps: (1) dissolving a carbohydrate in an acid solution, rapidly heating up and evaporating the solvent, so that the carbohydrate is dehydrated or partially dehydrated to obtain a pre-carbonized precursor; (2) carbonizing the precursor obtained in step (1) at a high temperature in an inert atmosphere to obtain a hard carbon material. The hard carbon material prepared by the present invention has a high specific capacity and first-cycle coulombic efficiency as a negative electrode material, as well as a fast charge and discharge capability and excellent cycle stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a hard carbon material and a preparation method and application thereof. Background Art

[0002] As the requirements for energy density and power density of secondary batteries in emerging technology fields such as electric vehicles, robots, drones, and large-scale energy storage are becoming increasingly higher, it is particularly important to simultaneously improve the energy density and power density of current lithium-ion batteries (LIBs) and sodium-ion batteries (SIBs) by developing new negative electrode materials. The interlayer spacing of graphite negative electrodes is low, and its rate performance is poor, which seriously affects the continued improvement of the current LIB power density. Hard carbon materials with relatively large carbon interlayer spacing have the ability to quickly deintercalate lithium ions and are the first choice for high-power density LIB negative electrode materials. In addition, due to the large interlayer spacing of hard carbon materials, reversible deintercalation of sodium ions can be achieved, and they have high specific capacity, making them the best choice for SIB battery negative electrode materials. Therefore, the development of low-cost and high-performance hard carbon negative electrode materials is crucial for both LIB and SIB batteries. However, achieving the unity of high mass / volume specific capacity and high rate performance of hard carbon materials remains a huge challenge.

[0003] The improvement of the rate performance of carbon negative electrode materials is mainly affected by the kinetics of ion and electron diffusion. For the ion diffusion process, nanostructures, porous or hollow structures can shorten the ion diffusion distance, while increasing the distance between carbon layers can reduce the ion diffusion resistance. The above structures can effectively promote the ion diffusion kinetics. However, all of the above methods inevitably lead to high specific surface area and low packing density, which ultimately leads to low initial coulomb efficiency (ICE) and unsatisfactory volumetric capacity. For improving the electron diffusion kinetics, sp 2 The hybridized carbon layer can conduct electrons efficiently, and the added conductive carbon can improve the electron conduction to a certain extent. Therefore, considering the kinetics of ion and electron diffusion, appropriately increasing the carbon layer spacing of hard carbon materials, reducing the nanoporous structure that the electrolyte can enter, and reducing the specific surface area are effective ways to achieve the unity of high mass / volume specific capacity and high rate performance of hard carbon materials. However, it is still difficult to prepare hard carbon materials with low cost, less nanoporous structure, and carbon layer spacing that can be regulated within a certain range. Summary of the invention

[0004] In order to improve the above technical problems, the purpose of the present invention is to provide a high-performance hard carbon material and a preparation method and use thereof.

[0005] The present invention provides the following technical solutions:

[0006] A method for preparing a hard carbon material comprises the following steps:

[0007] (1) dissolving a carbohydrate in an acid solution, rapidly heating the solution to evaporate the solvent, thereby dehydrating or partially dehydrating the carbohydrate to obtain a pre-carbonized precursor;

[0008] (2) Carbonizing the precursor obtained in step (1) at high temperature in an inert atmosphere to obtain a hard carbon material.

[0009] According to an embodiment of the present invention, in step (1), the carbohydrate is soluble, for example, selected from at least one of glucose, fructose, sucrose, galactose, lactose, maltose, soluble hemicellulose, pectin, trehalose, raffinose, stachyose, sorbitol, mannitol, xylitol, gluconic acid and water-soluble starch, for example, one, two or more.

[0010] According to an embodiment of the present invention, in step (1), the acid solution has dehydration properties, for example, one or a mixed solution of two or more selected from sulfuric acid, phosphoric acid, polyphosphoric acid, and selenic acid.

[0011] According to an embodiment of the present invention, in step (1), the concentration of the acid solution is 0.001 to 0.5 mol L -1 , preferably 0.01 to 0.2 mol L -1 , for example, 0.01 mol L -1 , 0.02 mol L -1 , 0.04 mol L -1 , 0.08 mol L -1 , 0.1 mol L -1 , 0.2 mol L -1 .

[0012] According to an embodiment of the present invention, the rapid heating refers to heating at a rate of 5 to 50°C min -1 Under the conditions of heating to the drying temperature and then keeping warm for a period of time.

[0013] Preferably, the drying temperature is 100-250°C, for example, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, 210°C, 220°C, 230°C, 240°C, 250°C.

[0014] Preferably, the insulation time is 2 to 24 hours, for example, 2 hours, 4 hours, 6 hours, 8 hours, 10 hours, 12 hours, 14 hours, 16 hours, 18 hours, 20 hours, 22 hours, or 24 hours.

[0015] Exemplarily, the drying temperature is 120-200° C., and the insulation time is 2-12 h, for example, 2 h, 4 h, 6 h, 8 h, 10 h, or 12 h.

[0016] According to an embodiment of the present invention, in step (2), the high-temperature carbonization temperature is 600-2000°C, for example, 600°C, 700°C, 800°C, 900°C, 1000°C, 1200°C, 1400°C, 1600°C, 1800°C, 2000°C; the holding time at the high-temperature carbonization temperature is 0.5-20h, for example, 2h, 4h, 6h, 8h, 10h, 12h, 14h, 16h, 18h, 20h.

[0017] Exemplarily, the high-temperature carbonization temperature is 800-1500° C., and the insulation time is 1-10 h, for example, 2 h, 4 h, 6 h, 8 h, or 10 h.

[0018] According to an embodiment of the present invention, the high temperature carbonization includes a heating stage and a heat preservation treatment. Preferably, after the temperature is raised to the high temperature carbonization temperature, the heat preservation treatment is performed.

[0019] According to an embodiment of the present invention, the temperature rising stage refers to heating to the high-temperature carbonization temperature at a certain heating rate.

[0020] Preferably, the heating rate is 0.1-20°C min -1 , preferably 0.5~10℃min -1 , for example 1℃min -1 、5℃min -1 .

[0021] According to an embodiment of the present invention, the preparation method further comprises: (3) crushing the hard carbon material prepared in step (2) into a suitable particle size.

[0022] According to an embodiment of the present invention, the particle size of the hard carbon material is 0.1-50 μm, preferably 1-30 μm, for example 22, 14, 25, 12 μm.

[0023] The present invention also provides a hard carbon material, which comprises a quasi-graphite structure and a pore structure composed of disordered carbon.

[0024] According to an embodiment of the present invention, the quasi-graphite structure is layered, wherein the (002) crystal plane interlayer spacing is 0.35 to 0.7 nm, preferably 0.35 to 0.5 nm, for example 0.5 nm.

[0025] According to an embodiment of the present invention, the size of the pore structure composed of disordered carbon is 0.35-0.7 nm, preferably 0.4-0.6 nm, for example, 0.394 nm, 0.391 nm, 0.422 nm, 0.397 nm, 0.388 nm, 0.384 nm, 0.386 nm, 0.396 nm, 0.385 nm.

[0026] According to an embodiment of the present invention, the hard carbon material is prepared by the above preparation method.

[0027] According to an embodiment of the present invention, the gram capacity of the hard carbon material is 200 to 650 mAh g -1 , for example, 250~600mAh g -1 , 200~450mAh g -1 For example, when the hard carbon material is applied to a lithium-ion battery, its gram capacity is 250 to 600 mAh g -1 For example, when the hard carbon material is applied to a sodium ion battery, its gram capacity is 200 to 450 mAh g -1 .

[0028] According to an embodiment of the present invention, the particle size of the hard carbon material is 0.1-50 μm, preferably 1-30 μm, for example, 22 μm, 14 μm, 25 μm, 12 μm, 10 μm, or 13 μm.

[0029] According to an embodiment of the present invention, the specific surface area of ​​the hard carbon material is 0.1 to 1000 m 2 g -1 , preferably 0.1 to 200 m 2 g -1 , for example, 17.3m 2 g -1 、21.4m 2 g -1 、253m 2 g -1 、32.3m 2 g -1 、5.7m 2 g -1 、156m 2 g -1 、132m 2 g -1 、20.2m 2 g -1 、18.4m 2 g -1 .

[0030] The present invention also provides a negative electrode material, which comprises the hard carbon material.

[0031] The present invention also provides an electrode, which comprises the hard carbon material and / or the negative electrode material.

[0032] According to an embodiment of the present invention, the preparation method of the electrode is as follows: the above-mentioned hard carbon material and / or negative electrode material is mixed with a binder and a conductive agent in a certain proportion to form a mixed slurry, the mixed slurry is evenly applied on a metal current collector, and dried to prepare the electrode.

[0033] According to an embodiment of the present invention, the conductive agent is selected from at least one of carbon black conductive agents, carbon fibers, Ketjen black, and carbon nanotubes.

[0034] According to an embodiment of the present invention, the binder is selected from at least one of sodium carboxymethylcellulose (CMC), styrene-butadiene rubber (SBR) and polyvinylidene fluoride (PVDF).

[0035] According to an embodiment of the present invention, the mass ratio of the hard carbon, the binder and the conductive agent is (60-95):(1-10):(1-30), preferably (80-90):(1-10):(5-10), for example, 80:5:5:10, 90:3:3:4.

[0036] According to an embodiment of the present invention, the metal current collector is selected from copper foil and / or aluminum foil.

[0037] The present invention also provides the application of the hard carbon material, negative electrode material or electrode, preferably in energy storage batteries.

[0038] The present invention also provides an energy storage battery, which includes the hard carbon material, negative electrode material or electrode.

[0039] According to an embodiment of the present invention, the energy storage battery is selected from at least one of a lithium ion battery, a sodium ion battery and a potassium ion battery.

[0040] According to an exemplary embodiment of the present invention, when the energy storage battery is a sodium ion battery, the electrode includes a metal current collector and the hard carbon material, wherein the metal current collector is selected from copper foil and / or aluminum foil.

[0041] According to an exemplary embodiment of the present invention, when the energy storage battery is a lithium-ion battery, the electrode includes a metal current collector and the hard carbon material, wherein the metal current collector is selected from copper foil.

[0042] According to an embodiment of the present invention, the energy storage battery further includes an electrolyte.

[0043] Preferably, the electrolyte is selected from at least one of ether electrolytes, ester electrolytes, gel electrolytes, solid polymer electrolytes, solid inorganic electrolytes or organic-inorganic composite electrolytes.

[0044] Beneficial Effects

[0045] The present invention uses soluble carbohydrate as raw material, dissolves it in a certain concentration of acid solution, increases the temperature to quickly dehydrate it to obtain a pre-carbonized precursor, and then carbonizes it at high temperature in an inert atmosphere to obtain a hard carbon material. The present invention uses soluble carbohydrate as raw material, which has extensive resources and low cost.

[0046] The present invention can remove most of the water in carbohydrates through the acid dehydration pre-carbonization process, so that the fluidity of the carbon precursor in the subsequent coking carbonization process is greatly reduced, the directional and orderly arrangement of carbon atoms is inhibited, and the generation of soft carbon with low crystal plane interlayer spacing is reduced, thereby achieving solid phase carbonization, thereby obtaining a hard carbon material with a relatively disordered structure and a hard carbon structure with a large crystal plane interlayer spacing. The hard carbon structure has a large number of sub-nanopore structures that cannot be entered by electrolytes and a crystal plane interlayer spacing of a quasi-hard carbon structure.

[0047] The present invention obtains a pre-carbonized precursor by regulating the type of carbohydrate, the amount and concentration of the acid solution, and the temperature of the reaction, and can regulate the hard carbon material, such as the pore size of the pore structure and the interlayer spacing of the quasi-hard carbon structure, through high-temperature carbonization temperature and heating rate. By further optimizing the parameters, a hard carbon negative electrode material with both high mass / volume specific capacity and excellent rate performance can be obtained, which promotes the improvement of the high-rate charge and discharge capacity of lithium-ion batteries and the development of the industrialization of sodium-ion batteries.

[0048] The hard carbon material prepared by the present invention as a negative electrode material has high specific capacity and first-cycle coulomb efficiency, as well as fast charge and discharge capability and excellent cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] Figure 1 A scanning electron microscope photograph of the hard carbon material after grinding in Example 1 is shown.

[0050] Figure 2 The XRD pattern of the hard carbon material in Example 1 is shown.

[0051] Figure 3 The charge and discharge curves of the assembled sodium ion battery in Test Example 1 are shown.

[0052] Figure 4 The rate performance of the assembled sodium ion battery in Test Example 1 is shown.

[0053] Figure 5 The charge and discharge curves of the assembled lithium-ion battery in Test Example 2 are shown.

[0054] Figure 6 The charge and discharge curves of the sodium ion battery in Test Example 3 are shown.

[0055] Figure 7 The cycle specific capacity diagram of the hard carbon material sodium ion battery in Test Example 4 is shown.

[0056] Figure 8 The rate comparison of the sodium ion battery in Test Example 3 is shown. DETAILED DESCRIPTION

[0057] The technical scheme of the present invention will be further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only exemplary descriptions and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope that the present invention is intended to protect.

[0058] Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available or can be prepared by known methods.

[0059] In the following examples, unless otherwise specified, M refers to mol L -1 .

[0060] Example 1

[0061] The preparation method of the hard carbon material is as follows: 4 g of glucose was dissolved in 15 mL of 0.04 M dilute sulfuric acid, and the resulting solution was placed in an oven at 10 °C min -1 The temperature was raised to 180°C at a rate of 100°C and kept at this temperature for 4 hours to obtain a pre-carbonized precursor. After drying, the obtained pre-carbonized precursor was placed in a tube furnace and heated at 5°C min -1 The temperature was raised to 1000°C at a heating rate of 200 °C and carbonized for 2 h. After natural cooling, the material was taken out and ground into powder to obtain a hard carbon material. Its properties are shown in Table 1.

[0062] The scanning electron microscopy of the hard carbon material of Example 1 is as follows Figure 1 As shown, XRD characterization Figure 2 As shown, 002 peak 2θ=22.5°, wherein the quasi-hard carbon structure is layered, and its (002) crystal plane interlayer spacing is 0.394nm, and the disordered carbon in the hard carbon material forms a sub-nanometer pore structure, and the pore size of the pore structure is 0.5nm.

[0063] Example 2

[0064] Preparation of hard carbon material: 4 g sucrose was dissolved in 15 mL 0.04 M dilute sulfuric acid and the resulting solution was placed in an oven at 10 °C min -1 The temperature was raised to 180°C and kept at this temperature for 4 hours to obtain a pre-carbonized precursor. After drying, the obtained pre-carbonized precursor was placed in a tube furnace and heated at 5°C min -1 The temperature was raised to 1000°C at a heating rate and carbonized for 2 h. After natural cooling, the material was taken out and put into a nylon ball mill for 5 min to obtain a hard carbon material. Its properties are shown in Table 1.

[0065] Example 3

[0066] Preparation of hard carbon material: 4 g of water-soluble starch was dissolved in 15 mL of 0.04 M dilute phosphoric acid, and the resulting solution was placed in an oven at 10 °C min -1 The temperature was raised to 180°C and kept at this temperature for 4 hours to obtain a pre-carbonized precursor. After drying, the obtained pre-carbonized precursor was placed in a tube furnace and heated at 5°C min -1 The temperature was raised to 1000°C at a heating rate of 200 °C and carbonized for 2 h. After natural cooling, the material was taken out and ground into powder. The material was washed with water for 2 to 5 times and dried to obtain a hard carbon material. The properties of the material are shown in Table 1.

[0067] Example 4

[0068] Preparation of hard carbon material: The hard carbon material was prepared according to the method described in Example 2, except that the carbonization temperature in the tube furnace was 900°C. The properties of the prepared hard carbon material are shown in Table 1.

[0069] Example 5

[0070] Preparation of hard carbon material: 4 g glucose was dissolved in 15 mL 0.04 M dilute sulfuric acid and the resulting solution was placed in an oven at 10 °C min -1 The temperature was raised to 180°C at a rate of 1°C and kept at this temperature for 4 hours to obtain a pre-carbonized precursor. After drying, the obtained pre-carbonized precursor was placed in a tube furnace and heated at 1°C min -1 The heating rate was increased to 500°C and then to 5°C min -1 The temperature was raised to 900℃ and carbonized for 2h. After natural cooling, the obtained material was taken out and ball-milled into powder to obtain a hard carbon material. The properties of the hard carbon material are shown in Table 1.

[0071] Example 6

[0072] Preparation of hard carbon material: 10 mL of 0.04 M dilute sulfuric acid and 5 mL of 0.04 M phosphoric acid solution were mixed evenly. 4 g of trehalose was dissolved in the prepared mixed acid solution, and the resulting solution was placed in an oven and dried at 80 °C for 24 h, then heated to 180 °C and kept warm for 4 h to obtain a pre-carbonized precursor. After drying, the obtained pre-carbonized precursor was placed in a tube furnace and heated at 5 °C min under an argon atmosphere. -1 The temperature was raised to 900°C at a heating rate of 1000 °C and carbonized for 2 h. After natural cooling, the mixture was taken out and ball-milled into powder. The powder was washed with water three times and dried to obtain a hard carbon material. The properties of the hard carbon material are shown in Table 1.

[0073] Example 7

[0074] Preparation of hard carbon material: Take 2g pectin and place it in 15mL of 0.01M dilute sulfuric acid, stir and dissolve it in an 80℃ oil bath. After dissolution, transfer it to an oven and heat it to 180℃ and keep it warm for 4h to obtain a pre-carbonized precursor. After drying, place the obtained pre-carbonized precursor in a tube furnace and heat it at 1℃min in an argon atmosphere. -1The temperature was raised to 1000°C at a heating rate of 200 °C and carbonized for 2 h. After natural cooling, the material was taken out and ball-milled into powder to obtain a hard carbon material. Its properties are shown in Table 1.

[0075] Example 8

[0076] The hard carbon material was prepared according to the method described in Example 1, except that the concentration of dilute sulfuric acid was 0.02 M. Hard carbon material 8 was prepared, and its properties are shown in Table 1.

[0077] Example 9

[0078] The hard carbon material was prepared according to the method described in Example 1, except that the concentration of dilute sulfuric acid was 0.08 M. Hard carbon material 9 was prepared, and its properties are shown in Table 1.

[0079] Comparative Example 1

[0080] Preparation of hard carbon material: 4 g glucose was dissolved in 15 mL water and the resulting solution was placed in an oven at 10 °C min -1 The temperature was raised to 180°C and kept at this temperature for 4 hours to obtain a pre-carbonized precursor. After drying, the obtained pre-carbonized precursor was placed in a tube furnace and heated at 5°C min -1 The temperature was raised to 1000°C at a heating rate of 200°C and carbonized for 2 hours. After natural cooling, the material was taken out and ball-milled into powder to obtain a comparative hard carbon material 1. Its properties are shown in Table 1.

[0081] Comparative Example 2

[0082] A hard carbon material was prepared according to the method described in Comparative Example 1, except that the carbonization temperature in the tubular furnace was 1200° C., to obtain a comparative hard carbon material 2, the properties of which are shown in Table 1.

[0083] Comparative Example 3

[0084] A hard carbon material was prepared according to the method described in Example 5, except that 4 g of glucose was dissolved in 15 mL of water to obtain a solution, and a comparative hard carbon material 3 was prepared, whose properties are shown in Table 1.

[0085] The pore structures of the hard carbon materials prepared in the above-mentioned Examples 2-9 are substantially the same as that in Example 1, and the pore sizes of the pore structures are all within the range of 0.35 to 0.7 nm.

[0086] The comparative hard carbon materials prepared in Comparative Examples 1-3 have not been dehydrated with an acid solution, so they will have a large volume expansion during the carbonization process, resulting in pore sizes ranging from 1 to 3 nm, and a small (002) crystal plane interlayer spacing in the formed quasi-hard carbon structure.

[0087] Test Example 1

[0088] Rate test: Take the hard carbon materials of Examples 1-9 and the comparative hard carbon materials in Comparative Examples 1-2 respectively, mix them with CMC, SBR and Super P conductive carbon black in a mass ratio of 80:5:5:10, apply them on copper foil, and use them as negative electrodes after vacuum drying. Use metal sodium sheets as counter electrodes, use Celgard 2325 as battery separators, and use diglyme+1M NaPF6 as electrolyte to prepare sodium / carbon half-cells in a glove box, which are respectively recorded as Battery 1A, Battery 2A, Battery 3A, Battery 4A, Battery 5A, Battery 6A, Battery 7A, Battery 8A, Battery 9A, Comparative Battery 1A, and Comparative Battery 2A.

[0089] The battery was tested for charge and discharge performance under the following conditions: constant current charge and discharge; current density was 0.02Ag -1 ; The discharge cut-off voltage is 0 V; the charge cut-off voltage is 2 V. The test results are shown in Table 1.

[0090] Figure 3 is the charge and discharge curve of battery 1.

[0091] Rate test: The above batteries were tested at currents of 0.1, 0.2, 0.5, 1, 2, 5, 10, and 0.2C, respectively. Figure 4 Shown are the rate test results of battery 1A, battery 8A and battery 9A, where 0.04M, 0.02M, and 0.08M correspond to battery 1A, battery 8A, and battery 9A, respectively.

[0092] Table 1 Performance of hard carbon materials of embodiments and comparative examples and performance of assembled sodium ion batteries

[0093]

[0094] When glucose is used to prepare the hard carbon material, it can be seen from Comparative Example 1 and Example 1 that the hard carbon material prepared without acid solution treatment has a larger specific surface area, (002) crystal plane interlayer spacing, and lower capacity and first efficiency.

[0095] It can be seen from Comparative Example 2 and Example 1 that when no acid solution treatment is performed, even if the carbonization temperature is increased, the specific surface area and (002) crystal plane interlayer spacing of the prepared hard carbon material are reduced, but the capacity and first efficiency are improved.

[0096] By comparing Examples 8 and 9 with Example 1, it can be seen that the different concentrations of the acid solution have an impact on the gram capacity of the prepared hard carbon material. -1 When the concentration of the acid solution is too high or too low, the gram capacity of the hard carbon material will decrease.

[0097] It can be seen from Examples 3, 5 and 6 that the hard carbon materials prepared by using different soluble carbohydrates have a higher specific surface area. Although the high specific surface area can provide a larger sodium ion storage adsorption capacity, some irreversible reactions will occur on the surface of the hard carbon material, resulting in a decrease in the first effect (first-cycle coulomb efficiency).

[0098] It can be seen from Table 1 that the batteries prepared from the hard carbon materials prepared in Examples 1-9 use an ether electrolyte with high coulombic efficiency. Although the first efficiency of the batteries is not much different, when the specific surface area of ​​the hard carbon material increases, the first efficiency of the batteries decreases accordingly.

[0099] Test Example 2

[0100] Constant current charge and discharge test: The hard carbon material, CMC, SBR and Super P conductive carbon black of Example 1 were mixed in a mass ratio of 80:5:5:10, coated on copper foil, and used as the negative electrode after vacuum drying. Metal lithium sheet was used as the counter electrode, Celgard 2325 was used as the battery separator, EC+DEC+DMC (1:1:1vol)+1vol%FEC+1M LiPF6 was used as the electrolyte to prepare a lithium / carbon half-cell, recorded as battery 1B.

[0101] The charge and discharge performance of battery 1B was tested under the following conditions: constant current charge and discharge; current density was 0.02A g -1 ; The discharge cut-off voltage is 0V; the charge cut-off voltage is 2V. The test results are as follows Figure 5 shown.

[0102] Test Example 3

[0103] Constant current charge and discharge test: The hard carbon material, CMC, SBR and Super P conductive carbon black of Comparative Example 1 were mixed in a mass ratio of 80:5:5:10, coated on copper foil, and used as the negative electrode after vacuum drying. A metal sodium sheet was used as the counter electrode, Celgard 2325 was used as the battery separator, and diglyme+1MNaPF6 was used as the electrolyte to prepare a sodium / carbon half-cell, which was recorded as Comparative Battery 1B.

[0104] The charge and discharge performance of the comparative battery 1B was tested under the following conditions: constant current charge and discharge; current density was 0.02A g -1 ; The discharge cut-off voltage is 0V; the charge cut-off voltage is 2V. The test results are as follows Figure 6 shown.

[0105] Test Example 4

[0106] Preparation of negative electrode: Referring to Test Example 1, the hard carbon material, CMC, SBR and Super P conductive carbon black of Example 4 were mixed in a mass ratio of 80:5:5:10, coated on aluminum foil, and used as the negative electrode after vacuum drying. A metal sodium sheet was used as the counter electrode, Celgard 2325 was used as the battery separator, and diglyme+1M NaPF6 was used as the electrolyte to prepare a sodium / carbon half-cell, recorded as battery 4A'.

[0107] The battery 4A' was tested for charge and discharge performance. The charge and discharge conditions were: constant current charge and discharge; current was 0.5C; discharge cut-off voltage was 0V; charge cut-off voltage was 2V. The test results are as follows: Figure 7 shown.

[0108] Test Example 5

[0109] Preparation of negative electrode: Referring to Test Example 1, the hard carbon material of Example 5 and the comparative hard carbon material 3, CMC, SBR and Super P conductive carbon black of Comparative Example 3 were mixed in a mass ratio of 80:5:5:10, coated on aluminum foil, and vacuum dried as the negative electrode. A metal sodium sheet was used as the counter electrode, Celgard 2325 was used as the battery separator, and diglyme+1MNaPF6 was used as the electrolyte to prepare a sodium / carbon half-cell, which were respectively recorded as Battery 5A' and Comparative Battery 3A'.

[0110] The battery 5A' and the comparative battery 3A' were tested for charge and discharge performance. The charge and discharge conditions were: constant current charge and discharge; current was 0.5C; discharge cut-off voltage was 0V; charge cut-off voltage was 2V. The test results are as follows: Figure 8 As shown, the pre-carbonized battery represents the battery 5A', and the non-pre-carbonized battery represents the comparative battery 3A'.

[0111] It can be seen from the rate tests and cycle tests of Test Examples 4 and 5 that when the hard carbon material prepared by the present invention is used as the negative electrode material, the battery has a good capacity retention rate under different current conditions.

[0112] The above is a description of the exemplary embodiments of the present invention. However, the protection scope of the present application is not limited to the above embodiments. Any modification, equivalent substitution, improvement, etc. made by those skilled in the art within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a hard carbon material, characterized in that: The preparation method comprises the following steps: (1) dissolving a soluble carbohydrate in an acid solution, rapidly heating and evaporating the solvent, so that the soluble carbohydrate is dehydrated or partially dehydrated to obtain a pre-carbonized precursor; the concentration of the acid solution is 0.02 to 0.08 mol L -1 The rapid heating refers to a heating rate of 5 to 50 ° C min -1 The temperature is raised to a drying temperature of 100 to 250° C. under the conditions and then kept warm for a period of time; the acid solution is selected from one or a mixed solution of two or more of sulfuric acid, phosphoric acid, polyphosphoric acid and selenic acid; (2) carbonizing the pre-carbonized precursor obtained in step (1) at high temperature in an inert atmosphere, and maintaining the temperature at a high temperature carbonization temperature of 600 to 2000° C. for 0.5 to 20 hours to obtain a hard carbon material; In step (1), the soluble carbohydrate is selected from at least one of glucose, fructose, sucrose, galactose, lactose, maltose, soluble hemicellulose, pectin, trehalose, raffinose, stachyose, sorbitol, mannitol, xylitol, gluconic acid and water-soluble starch; The hard carbon material comprises a quasi-graphite structure and a pore structure composed of disordered carbon; the quasi-graphite structure is layered, wherein the (002) crystal plane interlayer spacing is 0.35 to 0.7 nm; the size of the pore structure composed of disordered carbon is 0.35 to 0.7 nm.

2. The preparation method according to claim 1, characterized in that: In step (1), the rapid heating refers to heating at a rate of 5 to 50 °C min -1 The temperature is raised to the drying temperature under the conditions and then kept warm for a period of time; the drying temperature is 100-250°C; the holding time is 2-24h.

3. The preparation method according to claim 1, characterized in that: In step (2), the high temperature carbonization temperature is 800 to 1500° C., and the holding time is 1 to 10 hours; The high temperature carbonization includes a heating stage and a heat preservation treatment. After heating to the high temperature carbonization temperature, the heat preservation treatment is performed. The heating rate is 0.1-20°C min -1 .

4. The preparation method according to claim 3, characterized in that: The heating rate is 0.5-10°C min -1 .

5. The preparation method according to claim 1, characterized in that: The preparation method further comprises: (3) crushing the hard carbon material prepared in step (2) to a suitable particle size; The particle size of the hard carbon material is 0.1 to 50 μm.

6. The preparation method according to claim 1, characterized in that: The particle size of the hard carbon material is 1 to 30 μm.

7. A hard carbon material, characterized in that: The hard carbon material is prepared by the preparation method according to any one of claims 1 to 6.

8. The hard carbon material according to claim 7, characterized in that (002) interlayer spacing is 0.35-0.5 nm; The size of the pore structure composed of the disordered carbon is 0.4-0.6 nm.

9. The hard carbon material according to claim 7, characterized in that The gram capacity of the hard carbon material is 200 to 650 mAh g -1 ; The specific surface area of ​​the hard carbon material is 0.1 to 1000 m 2 g -1 .

10. The hard carbon material according to claim 7, characterized in that The specific surface area of ​​the hard carbon material is 0.1 to 200 m 2 g -1 .

11. A negative electrode material, comprising the hard carbon material according to any one of claims 7 to 10.

12. An electrode, characterized in that: The electrode comprises the hard carbon material according to any one of claims 7 to 10 and / or the negative electrode material according to claim 11.

13. Use of the hard carbon material according to any one of claims 7 to 10, the negative electrode material according to claim 11 or the electrode according to claim 12 in an energy storage battery.

14. An energy storage battery, characterized in that: The energy storage battery comprises the hard carbon material according to any one of claims 7 to 10, the negative electrode material according to claim 11 or the electrode according to claim 12.

Citation Information

Patent Citations

  • Preparation methods for high capacity biomass hard carbon anode material of sodium ion battery

    CN109921018A